Consistent concentrations of critically endangered Balearic shearwaters in UK waters revealed by at-sea surveys - Phillips, J; Banks, A; Bolton, M; Brereton, T; Cazenave, P; Gillies, N; Padget, O; van der Kooij, J; Waggitt, J; Guilford, T (Wiley, 2021)
Aim: Europe’s only globally critically endangered seabird, the Balearic shearwater (Puffinus mauretanicus), is thought to have expanded its post-breeding range northwards into UK waters, though its distribution there is not yet well understood. This study aims to identify environmental factors associated with the species’ presence, and map the probability of presence of the species across the western English Channel and southern Celtic Sea, and estimate the number of individuals in this area. Location: The western English Channel and southern Celtic Sea. Methods: This study analyses strip transect data collected from vessel-based surveys in the western English Channel and southern Celtic Sea during the shearwater’s post-breeding period between 2013 and 2017. Using environmental data collected directly and from remote sensors both Generalized Additive Models (GAMs) and the Random Forest (RF) machine learning model were used to determine shearwater presence at different locations. Results: Both models indicated that oceanographic features were better predictors of shearwater presence than fish abundance. Seafloor aspect, sea surface temperature, depth, salinity, and maximum current speed were the most important predictors. Based on the timing of the surveys (mainly in October) it is probable that most of the sighted shearwaters were immatures. Main conclusions: Areas with consistently high probabilities of shearwater presence were identified at the Celtic Sea front. Our estimates suggest that the study area in southwest Britain supports between 2% and 23% of the global population of Balearic shearwaters. This study provides the most complete understanding of Balearic shearwater distribution in UK waters available to date, information that will help inform any future UK conservation actions concerning this endangered 38 species.